2015
DOI: 10.3168/jds.2014-9037
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of prepartum dairy cows with β-carotene

Abstract: The prepartum supplementation of dairy cows with β-carotene was evaluated. Cows were blocked by parity and expected calving date and assigned to a treatment: β-carotene (1.2 g/cow per d) or control (no supplementation). The same total mixed ration batch was offered to all cows, and β-carotene was top dressed to individual cows once per day. The data set contained 283 Holsteins that received a treatment for >14 d (29.1±6.9 d). Frequency distributions were analyzed with the GENMOD procedure of SAS using logistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 27 publications
7
17
0
Order By: Relevance
“…Improved protein % was observed in colostrum of buffaloes Oliveira et al (2015) reported an increase in milk protein content from 2.90 to 2.96% when supplemented beta carotene @ 1.2 gram/day/cow for 14 days pre-partum. Nieto et al (2015) also reported that Colostrum protein concentration was affected by supplementation of vitamin E in Ewes (14.3% vs. 17.3%, P < 0.05).…”
Section: Colostrum Proteinmentioning
confidence: 92%
“…Improved protein % was observed in colostrum of buffaloes Oliveira et al (2015) reported an increase in milk protein content from 2.90 to 2.96% when supplemented beta carotene @ 1.2 gram/day/cow for 14 days pre-partum. Nieto et al (2015) also reported that Colostrum protein concentration was affected by supplementation of vitamin E in Ewes (14.3% vs. 17.3%, P < 0.05).…”
Section: Colostrum Proteinmentioning
confidence: 92%
“…The addition of βcarotene also had a positive effect on the size of ovarian follicles, which in turn means better fertility in cows. The addition of 1.2 g β-carotene per cow/day was associated with a lower incidence of retained placenta in multiparous cows and shorter time required for release of placenta (Oliveira et al, 2015). Serum β-carotene levels increased gradually postpartum in cows both with and without retained placenta, but their levels were significantly lower in cows with retained placenta compared to the control group.…”
Section: Resultsmentioning
confidence: 87%
“…β-carotene is important for cow fertility. Cows with higher blood β-carotene concentration in the postpartum period have shown higher fertility than cows with lower β-carotene (Oliveira et al, 2015). In addition, de Ondarza et al (2009) found higher fertility in cows fed extra β-carotene after calving.…”
Section: Resultsmentioning
confidence: 99%
“…The authors suggested that βC may positively effect on uterine involution, ovulation rates, progesterone concentrations, conception rates and may reduce the incidence of weak estrus expression, cystic ovaries, early embryonic loss (Kaewlamun et al, 2011;Ay et al, 2012;De Gouvêa et al, 2018;Madureira et al 2020). Previous studies reported that an increase in blood serum βC concentrations determined following parenteral administration of βC (Emre et al, 2018) and feed supplementation (Oliveira et al, 2015). Unfortunately, as a limitation of this field study, we did not collect or analyze blood samples after administration of βC, however, studies were reported that the blood βC concentration significantly higher one week after parenteral administration (Emre et al, 2018;Hye et al, 2020).…”
Section: Resultsmentioning
confidence: 99%